Hyperrealisme Identitas Fandom: Studi Virtual Etnografi terhadap Protes Fandom Seventeen Carat - Wicaksono, Ismail (CV. ITTC INDONESIA, 2025)
This research observes and examines Seventeen Carat's hyperreality on fandom identity that would sparks protest movement whenever there's changes in the identity through the theory perspective of Jean Baulliard's Revenge of The Crystal Theory using virtual enthography method on several fandom twitter account. The result of this research shows that the protest sparked initially because fans felt that identity change is a threat to their comfort hyperreality zone. The resistant move done by the fans to protest are through meme and comic shared in tweets. While on the other hand there are also prosumer fans who did different kind of movement by consuming the released product then alter and modificate the product to fulfill their satisfaction.